Disturbance regime alters the impact of dispersal on alpha and beta diversity in a natural metacommunity. Issue 11 (1st November 2013) - Vanschoenwinkel, Bram; Buschke, Falko; Brendonck, Luc
Abstract : Disturbance and dispersal are two fundamental ecological processes that shape diversity patterns, yet their interaction and the underlying mechanisms are still poorly understood, and evidence from natural systems is particularly lacking. Using an invertebrate rock pool metacommunity in South Africa as a natural model system, we studied potential interactive effects of disturbance regime and patch isolation on diversity patterns of species with contrasting dispersal modes (passive vs. active dispersal). Isolation and disturbance regime had negative synergistic effects on alpha diversity: both directly, by excluding late‐successional species from isolated patches; and indirectly, by modulating establishment success of generalist predators in well‐connected patches. Unimodal relationships between isolation and alpha diversity, as predicted by mass effects, were only detected for passive dispersers in frequently disturbed patches and not in active dispersers. For passive dispersers, indications for a positive effect of isolation and a negative effect of disturbance on beta diversity were found, presumably due to differences in deterministic succession and stochastic colonization–extinction dynamics among different patch types. Our findings illustrate that interactions between dispersal rates and disturbance regime are important when explaining species diversity patterns in metacommunities and support the idea that diversity in frequently disturbed habitats is more sensitive to effects of dispersal‐based processes.